Randomized Comparison of the Therapeutic Effect of Acupuncture, Massage, and Tachibana-Style-Method on Stiff Shoulders by Measuring Muscle Firmness, VAS, Pulse, and Blood Pressure. (25th February 2012) - Tachibana, Kazuhiro; Ueki, Noriyuki; Uchida, Takuji; Koga, Hiroshi
Abstract : To compare the therapeutic efficacy of acupuncture, massage, and Tachibana-Ryojutsu (one of Japanese traditional body balance therapy techniques (SEITAI)), on stiff shoulders, the subjects' muscle firmness, blood pressure, pulse, VAS, and body temperature were measured before and after the treatment. Forty-seven volunteer subjects gave written informed consent to participate in this study. The subjects were randomly divided into three groups to receive acupuncture, massage, or Tachibana-Ryojutsu. Each therapy lasted for 90 seconds. The acupuncture treatment was applied by a retaining-needle at GB-21, massage was conducted softly on the shoulders, and Tachibana-Ryojutsu treated only the muscles and joints from the legs to buttocks without touching the shoulders or backs. The study indicated that the muscle firmness and VAS of the Tachibana-Ryojutsu group decreased significantly in comparison with the acupuncture and massage groups after treatment.